Determination of Uranium by Neutron Activation Analysis and Delayed Neutron Counting - AL-Dayal, O.A. (Asian Journal of Chemistry, 2010)
Quantitative determination of uranium at low levels has many applications, e.g., in the environmental field, screening of soils, stream sediments, various water supplies, mining organisations in search of new sites, monitoring of run off from existing mines, personnel monitoring for those working with uranium from its raw ores to the purified element and assoicated compounds. In this work two analytical methods of uranium determination were used to analyze the same set of clay samples from various places from Al-Washime district. Both neutron activation analysis and, dela;yed neutron counting have been examined. The comparison was carried out to show the agreement and degree of accuracy between the two methods used.